Case report: A case of acute postoperative endophthalmitis following penetrating keratoplasty due to carbapenem-resistant Klebsiella Pneumoniae and literature review - Yuan, Ying; Liu, Xiaoyuan; Zhou, Li; Ding, Wuchun; Zhang, Liying; Zheng, Jinhua (Frontiers in Medicine, 2023)
A 22-year-old lady underwent penetrating keratoplasty for serious keratoconus. The following day, it was complicated by the development of infectious endophthalmitis. The source of infection was identified as carbapenem-resistant Klebsiella pneumoniae. The donor corneal button might be playing a role in infection transmission due to carbapenem-resistant Klebsiella pneumoniae in a sputum culture when the donor was still alive. Nosocomial infections were typically severe, rapidly progressive, and difficult to treat. Finally, the patient underwent therapeutic penetrating keratoplasty again with complete resolution of the infection.